2010
DOI: 10.1007/s10549-010-1078-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 5 positive cells represent a steroid receptor negative and therapy resistant subpopulation in luminal breast cancers

Abstract: A majority of breast cancers are estrogen receptor (ER) positive and have a luminal epithelial phenotype. However, these ER+ tumors often contain heterogeneous subpopulations of ER− tumor cells. We previously identified a population of cytokeratin 5 (CK5) positive cells within ER+ and progesterone receptor positive (PR+) tumors that is both ER−PR− and CD44+, a marker of breast tumor-initiating cells (TICs). These CK5+ cells have properties of TICs in luminal tumor xenografts, and we speculated that they are mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
128
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 38 publications
15
128
0
1
Order By: Relevance
“…MCF7 mammospheres were also shown to be resistant to high doses of tamoxifen (Cariati et al 2008). Moreover, tamoxifen, fulvestrant, or estrogen deprivation increased the percentage of cells expressing cytokeratin 5 (CK5), a marker of human breast stem/progenitor cells also found in BCSCs, in T47D breast cancer cells (Creighton Kabos et al 2011). These data confirm that, while endocrine therapies target the differentiated proliferative breast cancer cells, they cannot effectively target the BCSCs.…”
Section: Her2mentioning
confidence: 82%
See 1 more Smart Citation
“…MCF7 mammospheres were also shown to be resistant to high doses of tamoxifen (Cariati et al 2008). Moreover, tamoxifen, fulvestrant, or estrogen deprivation increased the percentage of cells expressing cytokeratin 5 (CK5), a marker of human breast stem/progenitor cells also found in BCSCs, in T47D breast cancer cells (Creighton Kabos et al 2011). These data confirm that, while endocrine therapies target the differentiated proliferative breast cancer cells, they cannot effectively target the BCSCs.…”
Section: Her2mentioning
confidence: 82%
“…In endocrine therapy, accumulating evidence suggests that there is an increase in BCSCs in ER C breast cancer following anti-estrogen treatment. Two studies have reported enrichment for cells with both BCSC gene and marker expression in breast tumor tissue following short term AI (letrozole) or tamoxifen treatment (Creighton et al 2010, Kabos et al 2011. Additionally, other studies demonstrated similar effects in ER C breast cancer cell lines.…”
Section: Her2mentioning
confidence: 95%
“…These cells, referred to here as "luminobasal" cells, have tumorinitiating potential. Similar cells are up-regulated in patients whose luminal tumors develop resistance to chemo-and hormone therapies (13).…”
Section: Ck5mentioning
confidence: 99%
“…We observed a histologic preference with half of serous and endometrioid carcinomas containing CK5+ cells, while in mucinous and non epithelial subtypes CK5 expression was infrequent. In breast cancer, ~50% of luminal ER+ tumors contain subpopulations of CK5+ cells where they show heightened endocrine and chemotherapy resistance (19). CK5 is expressed ubiquitously in basal-like breast cancer and is a signature marker of this subtype.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously identified that half of ER+ breast tumors contain a subpopulation of cells that express the epithelial-specific intermediate filament cytokeratin 5 (CK5) (18,19), a marker of luminal progenitor and stem cells in the normal breast (20,21). CK5+ compared to intratumoral CK5− cells are relatively quiescent, tumor initiating, and have enhanced endocrine and chemotherapy resistance (18,19).…”
Section: Introductionmentioning
confidence: 99%